The forgotten creed : Christianity's original struggle against bigotry, slavery, and sexism - Patterson, Stephen J., 1957- (Oxford University Press, 2018)
The first Christian creed said nothing about Christ, God, or salvation. Instead it told the followers of Jesus who they were: Children of God. Among them, distinctions of race, class, and gender would count for nothing. The Forgotten Creed is the story of that first, forgotten creed and its remarkable vision of human solidarity.